Inflammation and Hemostatic Activation may Contribute to Postsurgical Thrombosis in Patients With Bladder Cancer. (May 2016) - Abro, Schuharazad; Clark, Melanie; Barkan, Guliz; Hoppensteadt, Debra; Fareed, Jawed; Wojick, Eva; Quek, Marcus
The alterations of the inflammatory and thrombotic components in patients with cancer are not clearly understood. The purpose of this study was to profile markers of inflammation and thrombotic activation specifically in the patients with bladder cancer undergoing radical cystectomy. For this study, 134 samples were collected from patients undergoing radical cystectomy. Antiphospholipid antibodies (immunoglobulin G subtype), microparticles, and antiglycosaminoglycan antibodies were measured with a commercially available enzyme-linked immunosorbent assay kits. These biomarkers were compared in patients with bladder cancer and normal individuals (n = 20). Patients had an average value of 6.7 ± 11.9 ng/mL (median: 2.8, confidence interval: 4.69-8.75, and P value: .0038) of antiphospholipid antibodies versus normal individuals 1.96 ± 0.9 ng/mL (median: 1.8 and confidence interval: 1.5-2.35). Microparticles level in patients was 8.31 ± 6.14 ng/mL, (median: 6.1, confidence interval: 7.26-9.37, and P value: <.0001) versus normal individuals 3.57 ± 2.34 ng/mL (median: 2.85 and confidence interval: 2.476-4.664). The antiglycosaminoglycan antibodies in patients had an average value of 0.22 ± 0.1 optical density (OD; median: 0.2, confidence interval: 0.21-0.24, and P value: .0213) compared to normal individuals 0.25 ± 0.08 OD (median: 0.25 and confidence interval: 0.22-0.23). The correlation of antiglycosaminoglycan antibodies with antiphospholipid antibodies showed Spearman r value = .2364 (95% confidence interval: 0.05-0.4 and P value .009). The correlation of antiglycosaminoglycan antibodies versus microparticles showed Spearman r = −.195 (95% confidence interval: 0.37-0.01 and P value .0321). These data suggest that patients with bladder cancer have subclinical activation of thrombotic and inflammatory processes that may be further exacerbated by surgical procedures and lead to venous thromboembolism-related complications.